(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
I would like to take this opportunity to express my appreciation for the Journal of Pakistan Orthopaedic Association (JPOA), which is the official publication of the Pakistan Orthopaedic Association (POA). The JPOA is an essential platform for disseminating high-quality research and clinical knowledge in the field of Orthopaedics. It is registered with the Pakistan Medical and Dental Council and recognized by the Higher Education Commission (HEC) of Pakistan in the Y category. I am pleased to note that the JPOA is indexed with several prestigious databases, including Scope Med, Google Scholar, Eurasian Scientific Journal Index, ResearchBib, CiteFactor, DRJI, IJI Factor Indexing, Scientific Indexing, IP Indexing, PKP Index, ICMJE, National Digital Archive, and Pakmedinet. These achievements are a testament to the JPOA’s quality and rigor in publishing cutting-edge research and clinical insights. As the President of the Pakistan Orthopaedic Association, it is my honor to express my sincere admiration for the commendable efforts of Professor Zia Ullah Bajwa, the Editor-in-Chief of the Journal of Pakistan Orthopaedic Association (JPOA), and his editorial board members. Their hard work and dedication towards advancing the field of Orthopaedics in Pakistan and beyond is truly impressive. I would like to specifically acknowledge his efforts in promoting research and organizing manuscript workshops across the country, which have helped to encourage young surgeons to write and showcase their research work in JPOA. Such initiatives are essential in promoting and advancing the field of Orthopaedics, and I commend him for his vision and commitment towards achieving this. I would like to take this opportunity to urge all members and colleagues of the Pakistan Orthopaedic Association to continue supporting and contributing to JPOA. The high standards and impact of the journal are a testament to the collective efforts of its editorial board members, reviewers, authors, and readers. Let us continue to work together to uphold and enhance the reputation of JPOA and contribute to the advancement of the field of Orthopaedics. If any member wishes to hold a manuscript workshop at their Centre/Institute, they should submit their request to the POA Head Office at pakistanorthopaedicassociation@gmail.com as soon as possible. This will enable JPOA to arrange the workshop at the earliest possible date. Once again, I extend my heartfelt gratitude to Professor Zia Ullah Bajwa and his team for their exceptional work and dedication towards promoting and advancing the field of Orthopaedics in Pakistan and beyond.